Strategi Dan Model Pengembangan Usaha Peternakan Sapi Rancah - Suyudi Suyudi; Hendar Nuryaman; Erfan Erfan (Universitas Muhammadiyah Purworejo, 2016)
The development of the livestock sector is focused on the business of livestock farmers with an agribusiness perspective in an effort to increase the economy in rural areas. Local livestock that becomes germplasm in each region certainly have their respective advantages and potential. one of them is Cattle Ranch which is the native local livestock of West Java. The purpose of this research is to identify the strengths, weaknesses, opportunities, threats, and strategies as well as models in the development of the Ranch cattle business. The method used is a case study and developmental research. The Al Hidayah Livestock Group was selected purposively and is one of the pilot groups of Ranch Cattle in Ciamis Regency with a livestock population of 49 heads and group membership of 30 people, and the land owned by this livestock group is still very large so that it is still very potential to be developed. The results of research using SWOT analysis show a total score of Internal Factors Analysis Summary (strengths and weaknesses) and a score of External Factors Analysis Summary (opportunities and threats) of 3.060. and 3,143. Alternative strategies that can be applied include increasing the knowledge and ability of farmers by optimizing the availability of natural resources around; develop breeders' skills in collaboration with various related institutions in order to increase effectiveness and efficiency in raising livestock with the aim of increasing livestock productivity; absorb and apply a variety of information regarding the use of technology for optimal utilization of agricultural waste, and participate actively in various government programs such as the development of the People's Animal Husbandry Center (SPR). The development model consists of three main components, namely breeders/livestock groups, agribusiness systems, and institutions which are largely determined by the roles of breeders, extension agents, and institutions related to the development of scaffolding. Keywords: Scaffolding, SWOT, Strategy, Mode